f(x) = 6|x − 5|

f(−2

f(0)

f(1/2)

f(2)

f(x + 1

Please note that:

1) setting x= -2, I get f(-2) = 6 |-2-5| = 6*7=42;

2) setting x= 0, I get f(0) = 6|0-5| = 6*5 =30;

3) setting x= 1/2, I get f(1/2) = 6 | 1/2 -5 | = 6* (9/2) = 27;

4) setting x= 2, I get f(2) = 6 |2-5| = 6*3= 18;

5) setting x ---> x+1, I get f(x+1) = 6 | x+1-5| = 6 |x-4|;

6) setting x--->x^2 + 6, I get f(x^2+6) = 6 | x^2+ 6-5| = 6 |x^2 +1| = 6 (x^2 +1)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up